CHRISTIAN GERHARD LEOPOLD - N. A. Makatsariya (Акушерство, гинекология и репродукция, 2016)
The article highlights historic aspects of medical and research work of the German obstetrician of the XIX-XX centuries Christian Gerhard Leopold.